Probabilistic 3D modelling of shallow soil spatial variability using dynamic cone penetrometer results and a geostatistical method. Issue 2 (3rd April 2021) - Sastre Jurado, C.; Breul, P.; Bacconnet, C.; Benz-Navarrete, M.
ABSTRACT: Since soils are natural and non-homogeneous materials, spatial variability of their properties has been recognised as one of the main sources of uncertainties affecting geotechnical analyses. However, soil testing is limited and the description and quantification of the resulting soil variability still remain largely subjective in practice. In this paper, anapproach is proposed to rationally evaluate the soil spatial variability using field data provided by a site investigation programme based on a lightweight dynamic cone penetrometer test. The first part deals with the boundary identification of statistically mechanical homogeneous soil units. The second part focuses on modelling spatial variability through 3D conditional random fields in the homogeneous soil units previously identified. This approach has been applied to and studied in a real site investigation carried out in an alluvial Mediterranean deltaic environment.